The Use of Whole Brain Teaching Method in Improving Students’ Speaking Ability - Trisilia Devana (Universitas PGRI Semarang, 2020)
The objective of this research was to find out the improvement of students’ speaking skill teaching through Whole Brain Teaching method. The design used in this research was pre experimental. The population of this research was at the tenth grade students of SMK Negeri 2 OKU and the sample were which consisted of 36 students. The researcher used purposive sampling in taking the samples. The pre-test and post-test were used as the techniques for collecting the data. Instrument in this research was an oral speaking test. Based on the result of the pre- test, the mean score of the pre-test was 56.28. The result of the post-test the mean score was 68.89. Based on the statistical analysis, the researcher found that the value of Sig.= 0,000 less than the value of Significance level (a=0,05 and df = 35). It means that there was significantly improvement in teaching speaking by Whole Brain Teaching method at the the tenth grade students of SMK Negeri 2 OKU.